Broadband Nonlinear Photonics in Few‐Layer Borophene. Issue 7 (27th January 2021) - Ma, Chunyang; Yin, Peng; Khan, Karim; Tareen, Ayesha Khan; Huang, Rui; Du, Juan; Zhang, Ye; Shi, Zhe; Cao, Rui; Wei, Songrui; Wang, Xin; Ge, Yanqi; et al.
Abstract: In this paper, 2D borophene is synthesized through a liquid‐phase exfoliation. The morphology and structure of as‐prepared borophene are systemically analyzed, and the Z ‐scan is used to measure the nonlinear optical properties. It is found that the saturable absorber (SA) properties of borophene make it serve as an excellent broadband optical switch, which is strongly used for mode‐locking in near‐ and mid‐infrared laser systems. Ultrastable pulses with durations as short as 792 and 693 fs are successfully delivered at the central wavelengths of 1063 and 1560 nm, respectively. Furthermore, stable pulses at a wavelength of 1878 nm are demonstrated from a thulium mode‐locked fiber laser based on the same borophene SA. This research reveals a significant potential for borophene used in lasers helping extending the frontiers of photonic technologies. Abstract : 2D borophene is synthesized through a liquid‐phase exfoliation. The morphology and structure of as‐prepared borophene are systemically analyzed, and the excellent nonlinear optical properties of borophene are demonstrated through the Z ‐scan method. Ultrastable pulses can be successfully generated from borophene‐based mode‐locked fiber lasers at near‐ and mid‐infrared regimes.